(untitled) (International Journal of Engineering and Computer Science, 2015)
this paper, our main issue is an authorization and providing the data security for various applications in web services in a network. Cloud Computing is a revolutionary IT field and we are using this technology for various purposes. With the increasing use of the data sharing in distributed systems such as online social networks or cloud computing, there is increasing in concerns for data security while distributing or sharing data. Here, Ciphertext policy attribute-based Encryption(CP-ABE) is becoming cryptographic solution to above issue of secured data sharing among network. Also, we will have these achievements :1) key escrow problem could be solved by escrow-free key issuing protocol, where key is generated using the secure two-party computation between the key generation center and the data-storing center 2) fine-grained user revocation per each attribute could be done by using anonymous id algorithm where sharing of data will be done on attribute basis.